PERANCANGAN SISTEM ADMINISTRASI EAAA MOTORSHOP DENGAN METODE EXTREME PROGRAMMING - Syaiful Syafani (2022)
Eaaa Motorshop is a workshop that provides a variety of services. The Eaaa Motorshop workshop has not utilized and optimized information technology as a medium in conveying information and managing workshop data. There is also the purpose of this research to create and design an administrative information system using the Agile method with an Extreme Programming approach which emphasizes direct communication with the user so that it is flexible to rapid changes in the system. The system design uses the Laravel framework, MySQL as the database, and system testing is carried out using the Black Box Testing method. The results of this study are in the form of an Eaaa Motorshop administration system that can provide information and services to help improve the service quality of Eaaa Motorshop workshops.